The effect of teacher self-disclosure in improving ESL undergraduates argumentative essays - Paul Gnanaselvam Pakirnathan (2021)
This study was undertaken to find out if teacher self-disclosure could positively effect English asa Second Language (ESL) undergraduate students' writing performance in argumentative essays. Usingthe mixed-methods intervention design. both quantitative and qualitative data were collected inthis study. 75 undergraduates from three tutorial groups from an academic writing course at aMalaysian private institution of higher learning were selected as the experimental andcontrol groups through purposive sampling. The quasi-experimental pre-test-post-test design wasemployed to collect the undergraduates scores on argumentative essays while qualitative data weregathered using three methods, which were observation, focus group interview and one-to-oneinterview. The Pearson product-moment correlation and paired samples t-test were used forquantitative data analysis while thematic analysis was used for qualitative dataanalysis. The quantitative results indicated a significant difference in the post-testargumentative writing scores obtained between students from the experimental groups, Tl (t=-8.35, p